2018
DOI: 10.1016/j.psychres.2017.12.070
|View full text |Cite
|
Sign up to set email alerts
|

Computerized response inhibition training for children with trichotillomania

Abstract: Evidence suggests that trichotillomania is characterized by impairment in response inhibition, which is the ability to suppress pre-potent/dominant but inappropriate responses. This study sought to test the feasibility of computerized response inhibition training for children with trichotillomania. Twenty-two children were randomized to the 8-session response inhibition training (RIT; n = 12) or a waitlisted control (WLT; n = 10). Primary outcomes were assessed by an independent evaluator, using the Clinical G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Part II: Treatment or waitlist crossover (6–7 h total) . The game-like cognitive training program utilized in this phase was developed for a recent series of clinical trials studies and showed promise for improving RI in individuals with disorders characterized by poor RI ( Lee, Espil, Bauer, Siwiec, & Woods, 2018 ). See Table 2 for a description of the training program.…”
Section: Methodsmentioning
confidence: 99%
“…Part II: Treatment or waitlist crossover (6–7 h total) . The game-like cognitive training program utilized in this phase was developed for a recent series of clinical trials studies and showed promise for improving RI in individuals with disorders characterized by poor RI ( Lee, Espil, Bauer, Siwiec, & Woods, 2018 ). See Table 2 for a description of the training program.…”
Section: Methodsmentioning
confidence: 99%
“…Delivering therapist-guided behavior therapy entirely via the Internet, which has been successful for OCD (Andersson et al, 2012) and body dysmorphic disorder (Enander et al, 2016) could substantially increase the accessibility, and as we suggest above, enable even more patients to participate in treatment, in spite of full-time employment or other obstructive factors. Indeed, some promising results of computer or internet-delivered self-help treatments for TTM (Lee et al, 2018;Mouton-Odum et al, 2006;Rogers et al, 2014) and SPD (Flessner et al, 2007;Gallinat et al, 2019) have already been presented.…”
Section: Future Directionsmentioning
confidence: 99%
“…These monitors may be particularly helpful during the awareness and stimulus‐control components of HRT. A pilot clinical trial of computerized response inhibition training (RIT) in pediatric TTM patients demonstrated a 55% response rate using the Clinical Global Impression‐Improvement scale, though limited by a small sample size . The possibility of including technology in HRT may present an opportunity to target therapy at the unconscious pulling predominantly seen in the pediatric population.…”
Section: Ttm Managementmentioning
confidence: 99%
“…A pilot clinical trial of computerized response inhibition training (RIT) in pediatric TTM patients demonstrated a 55% response rate using the Clinical Global Impression-Improvement scale, though limited by a small sample size. 19 The possibility of including technology in HRT may present an opportunity to target therapy at the unconscious pulling predominantly seen in the pediatric population. Additional longitudinal studies would be helpful in demonstrating if lasting effects are maintained throughout adulthood.…”
Section: Electronic Devicesmentioning
confidence: 99%